Measuring Digital Teaching Competence of Academic Staff in Public Universities in Uganda - Mugizi, Wilson; Rwothumio, Joseph; Kasule, George W. (African Journal of Education, Science and Technology, 2023)
The unanticipated lockdown of campuses of universities caused by COVID-19 disrupted education worldwide. Nonetheless, the benefit that came with the lockdowns is that, while previously interest in online learning was an emerging unique mode of delivery used by particular institutions, it expanded to virtually all universities leading to large-scale digitizing of teaching and learning. However, in Uganda, public universities have been slow at digitizing their education compared to private universities. This study measured the digital competence of academic staff in public universities. Digital competence of academic staff was anchored in the UNESCO (2018) ICT Competency Framework for Teachers and the TPACK model. Digital teaching competence was measured in terms of course design, technical competence, communication competence, and time management competence. Using the survey design, data were collected from a sample of 327 academic staff from a population of 2225 academic staff from four public universities in Uganda using a self-administered questionnaire. Descriptive statistics and structural equation modelling using partial least squares structural equation modelling (PLS-SEM) were used to analyze the data. Descriptive results revealed that; course design, technical, communication and time management competences were high. PLS-SEM indicated that the four measures appropriate measures of digital competence. It was concluded that academics in public universities have the digital competences necessary for effective digitalization of education and technical, course design, course communication, and time management competences are appropriate measures for digital teaching competences. Therefore, the study recommended that managers of universities should take advantage of course design, technical, course communication and time management competences of academic staff to roll out digital education at a large scale. Also, scholars can use course design, technical, course communication and time management competences as measures of digital teaching competence.
Keywords: Communication; Competence; Course Design; Digital; Measures; Technical; Time Management